IMPLEMENTASI UNDANG-UNDANG NOMOR 18 TAHUN 2017 TENTANG PELINDUNGAN PEKERJA MIGRAN INDONESIA (PMI) TERHADAP KASUS KEKERASAN PMI DI ARAB SAUDI. - Deby Azizah, (2022)
Work is an important issue in human life, because with work, humans can meet the needs of life for themselves and their families. However, the limited number of job vacancies in Indonesia makes Indonesian citizens (WNI) choose to work abroad. However, the protection provided by the government in protecting PMIs working abroad has not been optimal considering the number of cases that befell PMIs working abroad. Cases of violence against Indonesian Migrant Workers (PMI) who are working abroad, especially Saudi Arabia, continue to occur even though the Indonesian government has updated the Law on the Protection of PMIs. The approach used in this research is a qualitative-descriptive approach, this approach was chosen because the role of the Government of Indonesia described in this study will involve several actors so as to produce a social interaction. This research focuses on how the implementation of Law no. 18 of 2017 concerning the protection of PMI as well as the obstacles and challenges faced by the government in its implementation. However, in reality the implementation of Law no. 18 of 2017 concerning the Protection of PMIs, many cases of violence that befell PMIs working in Saudi Arabia are PMIs who are placed non-procedurally. This is due to the lack of protection provided by the Government of Indonesia prior to the placement of PMIs to the destination country. Keyword: Protection, Indonesian Migrant Workers, Policies, Violence, United Arab Emirates.